Modularity clustering of economic development and ESG attributes in prefabricated building research - Li, Rita Yi Man; Li, Bo; Zhu, Xiaoe; Zhao, Jingjing; Pu, Ruihui; Song, Lingxi (Frontiers in Environmental Science, 2022)
One major change in the modern construction industry worldwide in recent years is moving toward prefabricated buildings (offsite construction) to achieve sustainable development. Despite an increase in attention to ESG due to global stock markets’ requirements and prefabricated buildings aid industries in achieving the ESG goal, few or even no research investigated the ESG attributes of the prefabricated buildings. Additionally, ESG subitems in different industries receive varying attention. Developed countries are primarily subject to ESG rules, but ESG laws in developing countries are at their infant stages. No study examined the effects of economic progress on prefabricated buildings’ ESG attributes. The research gaps are filled by visualising and clustering the WoS and Scopus articles’ keywords, themes, and authors’ locations. This article also studied the evolution of this field. Based on the science map modularity cluster analysis, cost control is the most concerned issue in developed and developing countries. There are far more articles related to sustainability and environmental aspects of prefabricated buildings. Although the governance aspects of prefabricated buildings have not been thoroughly studied, inadequate governance increases bond yields. Therefore, future research on prefabricated buildings may expand to governance aspect to benefit industry and academia.